1983
DOI: 10.1002/aja.1001680111
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of glucagonlike and gastric inhibitory polypeptidelike peptides in the pancreatic islets and gastrointestinal tract

Abstract: The distribution of cells displaying glucagonlike or gastric inhibitory polypeptide (GIP)-like immunoreactivity was examined in the pancreatic islets and gastrointestinal tracts of rats, dogs, and humans. A-cells in the pancreatic islets in all three species were stained by antisera having regional specificity for pancreatic-type glucagon, gut-type glucagon (glicentin), or GIP. Oxyntic A-cells of the gastric mucosa in dogs and humans also were stained comparably by these three antisera. In contrast, the K- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Studies concerning GIP immunoreactivity in A‐cells of pancreatic islets have been questioned because of the use of different antibodies with varying specificity (Smith et al,1977; Alumets et al,1978; Ahren et al,1981; Sjolund et al,1983; Smith,1983). It has been shown that members of the secretin‐glucagon family have a similar amino acid sequence near the N‐terminal part of the cDNA that encodes the active peptide (Kopin et al,1990) but are otherwise different.…”
Section: Discussionmentioning
confidence: 99%
“…Studies concerning GIP immunoreactivity in A‐cells of pancreatic islets have been questioned because of the use of different antibodies with varying specificity (Smith et al,1977; Alumets et al,1978; Ahren et al,1981; Sjolund et al,1983; Smith,1983). It has been shown that members of the secretin‐glucagon family have a similar amino acid sequence near the N‐terminal part of the cDNA that encodes the active peptide (Kopin et al,1990) but are otherwise different.…”
Section: Discussionmentioning
confidence: 99%
“…1979;Unger and Orci, 1981;Orci. 1982;Smith, 1983]. If the A cells were in cluded in the same category as the B cells, owing to the similarities of their secretory granules, without taking into account the granule sizes and the other cytological characteristics, the islets of both the dorsal and the ven tral lobe would be lacking in one of the cell types other wise identified with immunohistochemical methods, and the relative percentages of the various cell types would be absolutely mistaken.…”
Section: Discussionmentioning
confidence: 99%
“…4 Under normal conditions, this peptide might be converted to an insulin-like molecule by enzymatic systems common to both islet B-cells and salivary cells; 115 but, when affected by diabetogenic agents, IDCs might not properly cleave this precursor molecule, causing it to resist chemical extraction without necessarily influencing its immunostaining. 7 Insulin is secreted in the saliva of both animals and humans, 451314 and our results provide histologic evidence on the origin of salivary insulin-like material. Because salivary glands have been implicated as a potential source of circulating insulin, 41316 it seems reasonable to speculate that our findings of insulinlike immunoreactivity in parotid IDCs of two types of diabetic animals may help explain the so-called "honeymoon phase" of insulin secretion in human IDDM.…”
Section: Discussionmentioning
confidence: 57%